Restenosis risk factors after coronary stenting in metabolic syndrome patients - N. M. Danilov; T. T. Gorgadze; A. P. Savchenko; I. E. Chazova (Кардиоваскулярная терапия и профилактика, 2007)
This review is devoted to coronary restenosis after stent implantation in metabolic syndrome (MS) patients. It is known that some clinical factors increase restenosis risk, first of all, diabetes mellitus. Recently, MS has also been regarded as a pathology enhancing coronary restenosis risk. Certain MS features (reduced NO release after oral glucose tolerance test; increased leptin level; hyperinsulinemia, insulin resistance) are important predictors of intra-stent restenosis in coronary heart disease (CHD) patients with normal fasting levels of glucose and glycated hemoglobin. In CHD and MS patients, new, antiproliferative drug-coated stent use could be recommended.